The Role of International Law in Addressing Human Trafficking for the Purpose of Organ Trafficking: Implications for Global Health - Bunyamin, Bubun; Muslim, Thariq; Permana, Diki; Purnomo, Hadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Human trafficking for the purpose of organ trafficking has become a serious global problem that violates human rights and threatens global health. International law has an important role in efforts to combat this phenomenon by providing a legal framework that regulates and prohibits the practice of human trafficking and organ trafficking. In this paper, we explore the role of international law in addressing human trafficking for the purpose of organ trafficking and its implications for global health. We analyze various relevant international legal instruments, evaluate their implementation, and identify factors influencing the effectiveness of international law in combating human trafficking for the purpose of organ trafficking. We also provide suggestions to improve implementation of international law and protect global health from this harmful practice